Management of blood lipids in post-kidney transplant patients: a systematic review and network meta-analysis - Luo, Bohan; Zhong, Shan; Wang, Xiaoxiao; Guo, Pu; Hou, Yifu; Di, Wenjia (Frontiers in Pharmacology, 2024)
Introduction The primary objective of this systematic review was to provide an overview of the efficacy and safety of various lipid-lowering therapies in patients post-kidney transplant (PKT), given the limited existing literature. Considering the restricted number of available studies, this work aimed to summarize the existing evidence regarding the effectiveness of different lipid-lowering treatments in PKT patients. The effects of various lipid-lowering therapeutic regimens on lipid levels were compared, and their safety was assessed, with the heterogeneity of treatment protocols acknowledged. Material and Methods Randomized controlled trials investigating different treatment regimens (DTRs) for regulating lipid levels in PKT patients were systematically retrieved from PubMed, Cochrane Library, and Embase, from inception to March 2024. Literature quality was assessed employing the Cochrane risk of bias assessment tool. Data analysis and graphical representation were performed employing RevMan5.3 and Stata 20.0. The surface under the cumulative ranking area (SUCRA) compared the effects of DTRs on lipid profiles, incidence of adverse events, and all-cause mortality in PKT patients. Results Fifteen studies were included, comprising 5,768 PKT patients and involving 9 treatment regimens. The results revealed that, for changes in high-density lipoprotein cholesterol (HDL-C), the SUCRA rankings from highest to lowest among PKT patients receiving DTRs were statins + ezetimibe (70%), placebo (61.5%), fibrates (57.2%), statins (44.1%), and fish oil (17.3%). Regarding changes in low-DL-C (LDL-C), the SUCRA rankings from highest to lowest among PKT patients receiving DTRs were statins (68.2%), statins + ezetimibe (67.5%), fish oil (53.4%), fibrates (34.5%), and placebo (26.5%). For the change in total cholesterol (TC) levels, a network meta-analysis (NMA) revealed that among PKT patients receiving DTRs, the SUCRA rankings from highest to lowest for TC change were statins + ezetimibe (97.6%), proprotein convertase subtilisin/kexin type 9 inhibitors (PCSK9 inhibitors) (74.3%), fish oil (64.3%), statins (61.6%), fibrates (47.2%), placebo (31.6%), calcineurin phosphatase inhibitors (11.9%), and immunosuppressants (11.4%). Regarding the change in triglyceride (TG) levels, a NMA showed that among PKT patients receiving DTRs, the SUCRA rankings from highest to lowest for TG change were fibrates (99.9%), statins (68.9%), PCSK9 inhibitors (66.6%), statins + ezetimibe (55.1%), placebo (49.2%), fish oil (45.0%), immunosuppressants (7.8%), and calcineurin phosphatase inhibitors (7.6%). For the occurrence of kidney transplant failure, a NMA revealed that among PKT patients receiving DTRs, the SUCRA rankings from highest to lowest for reducing the incidence of kidney transplant failure were PCSK9 inhibitors (69.0%), calcineurin phosphatase inhibitors (63.0%), statins (61.5%), placebo (55.1%), steroids (51.8%), immunosuppressants (27.1%), and fibrates (22.5%). Regarding all-cause mortality, a NMA showed that among PKT patients receiving DTRs, the SUCRA rankings from highest to lowest for reducing all-cause mortality were PCSK9 inhibitors (90.5%), statins (55.8%), and placebo (3.7%). Conclusion In reducing lipid levels in PKT patients, combination therapy with statins and ezetimibe demonstrated notable advantages and higher effectiveness. PCSK9 inhibitors exhibited greater advantages in reducing adverse events and mortality rates in PKT patients, with higher safety.